PERFORMANCE OF ISLAMIC INDICES: RISK ADJUSTED RETURNS OF SHARIA COMPLIANT STOCKS ON JAKARTA ISLAMIC INDEX AND DOW JONES ISLAMIC TURKEY - Banani, Ade; Hidayatun, Nur Afni (Journal Economics & Business Atmajaya Indonesia, 2017)
The purpose of this research was to analyze the performance of Islamic indices compared to their counterparts. The research elaborated the performance of Islamic index in developing countries, which were Indonesia and Turkey represented by Jakarta Islamic Index and Dow Jones Islamic Market Turkey. This research was conducted during the period of 2010 until 2014. Populations in this research were all of companies listed in Jakarta Islamic Index, Dow Jones Islamic Market Turkey and their counterpart index. While sample was determined by purposive sampling method to eliminated stocks listed in both Islamic and counterpart index (dual listing). Data collection techniques used was method of documentation, literature review and internet search. The result based on three risk adjusted performance measurements consist of Sharpe, Treynor and Jensen Alpha, Islamic index did not significantly result in poor performance compared to its counterpart. Moreover, Islamic index in Indonesia has insignificantly outperformed its counterpart LQ45 index, while in Turkey has insignificantly underperformed it counterpart Dow Jones Turkey Titans 20 index. This study also revealed that Sharia compliant did not significantly affect the performance of Islamic index related to risk and return payoffs. Therefore, investors who are concerns with investing in Sharia compliant stocks could also benefit by holding portfolio of investments adhering to Sharia principles.